Al-Marsad Right as a Mechanism for Developing and Investing in Urban Waqf Properties in Algerian Legislation - Djelloul Mehda (Atebe)
The Al-Marsad (observatory) contract holds significant importance as a means for developing and investing in urban Waqf (endowment) lands. It serves as an exception when the endowment lacks the resources to independently develop the land. Under this right, private capital can be utilized, with the proceeds from construction benefiting the Waqf. The observatory owner can recover their construction expenses along with profits. Importantly, the investment value remains a debt secured by the Waqf. Unlike direct ownership, the observatory right is not a real property right stemming from Waqf ownership. Instead, it is a unique personal right that allows the owner to exploit the building, transfer it to others, and pass it on to heirs within the bounds of creditor rights. Although it intersects with provisions related to newly established exploitation contracts, its distinct nature makes it an effective method for developing and investing in Waqf properties, necessitating legislative regulation